Descriptive Analysis of Attitude Towards Students READY Programme - Banwari Lal Shah,; Rekha Rani,; Sheetal,; Sunil Kumar, (Indian Journal of Extension Education, 2023)
The 5th deans committee of ICAR has framed a comprehensive student READY programme syllabus for all of the agricultural and allied disciplines. It is a crucial component of the four-year bachelor's degree programme in agriculture offered by all colleges. It shows a lot of promise for producing better agricultural technocrats with a high degree of expertise combined with a contemporary approach and improved managerial abilities. This study was done to find out how students felt about the Student READY programme and how it related to the student's character attributes. The three collage of agriculture university Jodhpur i.e. Jodhpur, Nagaur, and Sumerpurwere purposively selected and data were collected from 140 undergraduate students. The results indicated that most students have a positive opinion of the Student READY programme and that there is a strong correlation between the programme and personal characteristics. The study's findings indicate that this program improved people's capacity for interpersonal and professional problem-solving as well as their communication and personality development.